Applied Technology and Innovation Management Insights and Experiences from an Industry-Leading Innovation Centre - Arnold, Heinrich.; Erner, Michael.; Mc̲kel, Peter.; Schlf̃fer, Christopher. (Springer Berlin Heidelberg, 2010)
Rapid application of new technologies and highly leveraged innovation processes are key for the success of companies and organizations in dynamic markets. Based on the experiences of one of the industry<U+0019>s most modern innovation centers this book provides an insight into the tools and methods used to align customer requirements, competitive challenges and technological development. Both, scientists and practitioners, will benefit from the lessons learned and presented in this volume.